2023
DOI: 10.1111/dom.14982
|View full text |Cite
|
Sign up to set email alerts
|

Identifying diabetogenic drugs using real world health care databases: A Danish and Australian symmetry analysis

Abstract: Aims Drug‐induced diabetes is underreported in conventional drug safety monitoring and may contribute to the increasing incidence of type 2 diabetes. Therefore, we used routinely collected prescription data to screen all commonly used drugs for diabetogenic effects. Methods Leveraging the Danish nationwide health registries, we used a case‐only symmetry analysis design to evaluate all possible associations between drug initiation and subsequent diabetes. The study was conducted among individuals aged ≥40 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…databases containing information on individual drug users are increasingly used for screening and evaluating unknown drug effects. [4][5][6][7][8] In addition, evaluating drug utilization patterns by epidemiological measures and by assessment of inequality in drug use may be an important tool for identifying inappropriate or unexpected drug use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…databases containing information on individual drug users are increasingly used for screening and evaluating unknown drug effects. [4][5][6][7][8] In addition, evaluating drug utilization patterns by epidemiological measures and by assessment of inequality in drug use may be an important tool for identifying inappropriate or unexpected drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, suboptimal or wrongful use is less obvious and may only be discovered by intentional efforts such as surveillance or screening 3 . Real‐world healthcare databases containing information on individual drug users are increasingly used for screening and evaluating unknown drug effects 4–8 . In addition, evaluating drug utilization patterns by epidemiological measures and by assessment of inequality in drug use may be an important tool for identifying inappropriate or unexpected drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been reported diabetogenic effects of several drug classes such as, glucocorticoids, β-blockers, second-generation antipsychotics, thiazides, and statins (Lund et al, 2023). Statins are the gold standard prevention of cardiovascular diseases and treatment of dyslipidemia, which are associated with increase in the incidence of type 2 diabetes in treated individuals (Galicia-Garcia et al, 2020;Needamangalam Balaji et al, 2022;Robinson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental, occupational, and medicinal exposures with diabetogenic agents have been associated with increased risk of type 2 diabetes (Filippini et al, 2022; Jagai et al, 2020; Kolb & Martin, 2017; Leso et al, 2017). Previous studies have been reported diabetogenic effects of several drug classes such as, glucocorticoids, β‐blockers, second‐generation antipsychotics, thiazides, and statins (Lund et al, 2023). Statins are the gold standard prevention of cardiovascular diseases and treatment of dyslipidemia, which are associated with increase in the incidence of type 2 diabetes in treated individuals (Galicia‐Garcia et al, 2020; Needamangalam Balaji et al, 2022; Robinson, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence difference is an absolute measure and conveys the potential public health impact of a given association. Hitherto, this difference has been calculated from the observed data, 4,5 but this approach may be biased if not adjusted for the null-effect SR. Therefore, we propose to calculate an adjusted difference.…”
mentioning
confidence: 99%